2003
DOI: 10.1366/000370203322102906
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Wavelength Mid-Infrared Micro-Spectral Imaging Using Semiconductor Lasers

Abstract: Infrared (IR, 3-12-microm) microscopic spectral imaging is an important analytical technique. Many current instruments employ thermal IR light sources, which suffer the problem of low brightness and high noise. This paper evaluates the system engineering merit in using semiconductor lasers, which offer orders-of-magnitude-higher power, brightness, and lower noise. A microscopic spectral imaging system using semiconductor lasers (quantum cascade) as illuminators, and focal plane array detectors demonstrated a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…Lasers have been widely used for spectroscopic analyses 108 for a number of years and, similarly, various studies have used QCLs for IR spectroscopy 109,113 as well as microscopy and imaging. 114,115 The most widely reported studies in spectroscopy have been focused on using the narrow-band properties and high intensity of the QCL to profile specific species, aqueous environments 116,118 or the integrated and compact instrumentation 119,120 that may be developed for specific experimental configurations 121 or applications. 122,124 The technology has made rapid progress, specifically in spectral properties and power.…”
Section: Data Recording: Instrumentationmentioning
confidence: 99%
“…Lasers have been widely used for spectroscopic analyses 108 for a number of years and, similarly, various studies have used QCLs for IR spectroscopy 109,113 as well as microscopy and imaging. 114,115 The most widely reported studies in spectroscopy have been focused on using the narrow-band properties and high intensity of the QCL to profile specific species, aqueous environments 116,118 or the integrated and compact instrumentation 119,120 that may be developed for specific experimental configurations 121 or applications. 122,124 The technology has made rapid progress, specifically in spectral properties and power.…”
Section: Data Recording: Instrumentationmentioning
confidence: 99%
“…The quantum cascade (QC) laser has emerged as a high performance semiconductor laser for MIR spectroscopy, offering high output power and high spectral radiance in a compact and robust device. 11 Early uses of QC lasers in microscopic chemical imaging capitalized on their high brightness, 12 but were limited by a small wavelength tuning range. The ECQCL source overcomes this limitation by providing a tuning range of 10% to 20% of its center wavelength or greater.…”
Section: Introductionmentioning
confidence: 99%
“…For practicality, they are robust, compact, and potentially low cost. Advanced MIR semiconductor lasers have been demonstrated for tissue imaging, 27 and application for conjunctiva glucose measurement is being developed. 24 A potential issue with MIR lasers is the lack of large spectral coverage, but some studies have shown that only a few wavelengths may be needed.…”
Section: Introductionmentioning
confidence: 99%
“…24 A potential issue with MIR lasers is the lack of large spectral coverage, but some studies have shown that only a few wavelengths may be needed. 11,13,24 Also, recent progress in tunable MIR lasers [27][28][29][30][31] promises broad wavelength coverage.…”
Section: Introductionmentioning
confidence: 99%